Nutrient free flaps with vascular bypasses for extremity salvage in patients with chronic limb ischemia - Horch, Raymund E.; Lang, Werner; Arkudas, Andreas; Taeger, Christian; Kneser, U.; Schmitz, Marweh; Beier, Justus (Journal of Cardiovascular Surgery, 2014)
Treatment of severe wounds remains a surgical challenge in patients with critical limb ischemia (CLI). In some patients with end stage disease a combined arterial and venous vascular bypass together with immediate or subsequent free soft tissue transfer can become necessary to salvage the limb. The aim of this paper was to develop an algorithm of differential approaches of interdisciplinary reconstructions with bypasses and free flaps for leg salvage.From our experiences with over 76 patients receiving a vascular bypass and a free microsurgical tissue transfer, we analyzed the various configurations of possible vascular constellations and treatment options. We derived an algorithm for the combined interdisciplinary surgical approach.We found the surgical technique to be one of the main predictors for the final outcome and categorized the various options and vascular configurations in combination with free flaps to salvage extremities. The overall complication rate with more than 20% revisional surgeries is higher than in routine free flap transfer for reconstructions in patient without CLI. We observed 3 failures (4%) with complete flap loss and bypass occlusion and found 3 patients (4%) with initially successful reconstructions to have secondary amputations within 6 to 18 months postoperatively.Given the multitude of concomitant diseases in patients with serious wounds and CLI the distinct choice of the individual reconstructive vascular/flap-procedure has to be thoroughly selected. Any treatment decision against revascularization must be made only with proper and adequate diagnosis based on proper and sufficient diagnostic imaging techniques following an interdisciplinary discussion of possible options for limb salvage. Based on our experience with a large series of this type of combined revascularization-flap reconstruction we developed a specific algorithm of surgical variants of bypass-free flap arterial and venous reconstructions that is presented in this paper.
EVALuna2:15174